Insights on FTD: An externally led patient‐focused drug development meeting. (December 2021) - Niehoff, Debra; Dodge, Shana G; Graham, Elizabeth; Barker, Megan S; Cosentino, Stephanie; Wheaton, Dianna KH; Denny, Sharon S; Dacks, Penny A; Dickinson, Susan
Abstract: Background: Understanding the lived experience of those affected by a disorder should be central to the development and evaluation of therapeutics. Disease‐specific Externally Led Patient‐Focused Drug Development (EL‐PFDD) meetings were established by the FDA to hear directly from those living with a condition about experiences, symptoms, treatments, and hopes for new therapies. Such insights are particularly important for frontotemporal degeneration (FTD), a genetically and clinically heterogenous condition that includes behavioral variant FTD (bvFTD), primary progressive aphasias, progressive supranuclear palsy, corticobasal syndrome, and ALS with FTD. Method: On March 5, 2021, AFTD hosted an EL‐PFDD for FTD; 382 caregivers, family members, and persons with FTD participated, plus 171 professionals. In preparation, AFTD and the FTD Disorders Registry conducted the FTD Insights Survey, gathering information on clinical and genetic characteristics of respondents; the earliest, current, and most concerning symptoms; and perspectives on treatments and clinical trials. 1, 237 persons with FTD, care partners/caregivers, and family members in the US, Canada and UK had completed the survey by October 31, 2020. Result: People living with all FTD syndromes described challenges in activities of daily life, including preparing meals, managing finances, driving, and conversing. Symptoms vary within and across disorders, encompassing language, motor function, thinking/decision‐making, interpersonal/emotional functioning, among others. Many people diagnosed have limited awareness of their symptoms (65% bvFTD; 37% other FTD disorders). In genetic FTD, the path to diagnosis can be simpler, yet a lifetime of perceived or known risk can dramatically influence life decisions. The lack of effective, approved therapies – disease‐modifying or symptomatic – was a universal concern. Non‐prescription and off‐label prescription therapies may stabilize symptoms temporarily while prescribed acetylcholinesterase inhibitors can exacerbate symptoms. Many people are willing to participate in clinical research depending on illness stage and burden imposed by trial design. Conclusion: The community of those affected by FTD offers insights into this condition as partners in research. Central themes of the EL‐PFDD meeting for FTD will be summarized by AFTD in a Voice of the Patient reported submitted to the FDA. Results of the FTD Insights Survey are available to researchers through the FTD Disorders Registry.